Laparoscopic suture repair of idiopathic gastric perforation in Duchenne muscular dystrophy - Go Miyano; Hiroshi Nouso; Keiichi Morita; Hideaki Nakajima; Mariko Koyama; Masakatsu Kaneshiro; Hiromu Miyake; Masaya Yamoto; Koji Fukumoto; Naoto Urushihara (Wolters Kluwer Medknow Publications, 2015)
We report herein an adolescent case of Duchenne muscular dystrophy (DMD) with idiopathic gastric perforation, in which emergency surgical repair was performed laparoscopically. A 14-year-old nonambulatory boy with DMD was brought to our emergency department with sudden onset of severe abdominal pain and distention. Plain radiograph and computed tomography confirmed the presence of free intraperitoneal air and intrapelvic effusion. The patient elected to undergo laparoscopic inspection with 4 trocars, revealing a focal perforation, 3-4 cm in diameter, on the upper gastric body near the diaphragm. The stomach was also found to have a thin wall without evidence of peptic ulcer disease or other abnormalities. An interrupted suture was placed using 4-0 PDS. The abdomen was extensively irrigated, and multiple J-Vac drains were left in situ. Total operation time was 90 min, and no intraoperative complications were encountered. Enteral feeding through a nasogastric tube was started on postoperative day 7. The postoperative course has been uneventful as of the 12-month follow-up. Pediatric surgeons should be aware of the increased risk of gastric perforation associated with DMD, and that laparoscopic repair can be safely performed even in emergency settings.